A Penetrating-Anchoring Mathematical Model for the Soft Asteroid Anchoring System - Zhijun Zhao; Shuang Wang; Jingdong Zhao (International Journal of Aerospace Engineering)
The asteroid landing mechanism is necessary to be anchored to avoid flowing away. At present, the study on the anchoring system is mainly focused on the mechanical design, but there are few researches on the penetrating or anchoring mathematical model, and the researches on combining two models with each other are even more lacking. In the paper, based on the characteristics of Mohr-Coulomb material, a penetrating mathematical model of the anchoring system is established. This penetrating mathematical model can be used to calculate the penetrating depth of the anchor body according to the penetrating speed and the medium properties. Secondly, an anchoring mathematical model is established, which shows the relationships among the anchoring force, medium properties, and penetrating depth. Finally, a penetrating-anchoring mathematical model is built with the penetrating depth as the link. The model establishes a relationship between the anchoring force and the initial penetrating conditions.